Úlcera venosa na atenção primária: saberes e práticas de equipes de enfermagem - Robaina, Marianne Lopes (2016)
The venous ulcers represent larger chronic injuries of the lower limbs and cause changes in the lives of affected people, have high rates of recurrence and chronicity. The nursing team is responsible for the implementation and evaluation of dressings, in addition, it is important that the team provides information on caring for the injury and guidelines to help the healing and cessation of relapses. This research objective to identify the knowledge and care practices, nursing teams of primary care in the city of Santa Maria, Rio Grande do Sul, Brazil on venous ulcer. This is a qualitative research, data collection, held in June and July 2015, was carried out through semi-structured interviews with nurses and nursing technicians and observation with passive and directed participation, during the course of curative; It was attended Basic Units nursing teams; the analysis was done using the operative proposal to Minayo. The research took place after approval by the County Health Department of Santa Maria and the Research Ethics Committee of UFSM. The guidelines were considered involving human research, contained in Resolution 466/2012 of the National Health Council. All professionals have demonstrated knowledge of the circulatory origin of the lesion; professionals, especially nurses, demonstrated extensive knowledge about the importance of the guidelines for the improvement of venous ulcers; among the difficulties mentioned, the lack of material was the most frequently cited by participants; the family was cited as an important ally in the care of people with venous ulcers; the link between the professional and the patient contributes to the guidelines are followed best; professionals seek to help each other in the face of difficulties or questions encountered; nurses participate more training on skin lesions than the nursing technicians. With this study, it was possible to deepen the knowledge of nursing practice in this area, providing new insights, favoring the quality of care provided to people with venous ulcers.